Synthesis of amphiphilic poly(methyl methacrylate-b-ethylene oxide) copolymers from monohydroxy telechelic poly(methyl methacrylate) as macroinitiator - Dhara, Mahua Ganguly; Baskaran, Durairaj; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
The synthesis of well-defined poly(methyl methacrylate)-block-poly(ethylene oxide) (PMMA-b-PEO) dibock copolymer through anionic polymerization using monohydroxy telechelic PMMA as macroinitiator is described. Living anionic polymerization of methyl methacrylate was performed using initiators derived from the adduct of diphenylethylene and a suitable alkyllithium, either of which contains a hydroxyl group protected with tert-butyldimethylsilyl moiety in tetrahydrofuran (THF) at -78 degrees C in the presence of LiClO4. The synthesized telechelic PMMAs had good control of molecular weight with narrow molecular weight distribution (MWD). The H-1 NMR and MALDI-TOF MS analysis confirmed quantitative functionalization of chain-ends. Block copolymerization of ethylene oxide was carried out using the terminal hydroxyl group of PMMA as initiator in the presence of potassium counter ion in THF at 35 degrees C. The PMMA-b-PEO diblock copolymers had moderate control of molecular weight with narrow MWD. The H-1 NMR results confirm the absence of trans-esterification reaction of propagating PEO anions onto the ester pendants of PMMA. The micellation behavior of PMMA-b-PEO diblock copolymer was examined in water using H-1 NMR and dynamic light scattering. (C) 2008 Wiley Periodicals, Inc.
Keywords: Anionic polymerization; block copolymers; synthesis